Characterizing Occupational Injuries Among Sawmill Workers Of Agbogbloshie Timber Market, Accra - Brefo, A.A. (University of Ghana, 2017)
Background: The wood products industry historically has been considered to be one of the most dangerous industries for construction employees, especially sawmill workers. Sawmill workers are exposed to several occupational injuries including burns, cuts, breathing disorders, noise pollution, electrocution, etc., which can have serious consequences on the health of workers. Objective: The study characterized occupational injuries among sawmill workers of the Timber market. Methods: The study was a cross-sectional study using structured interviewer administered questionnaire as a survey instrument. The study randomly picked sawmills’ workers while they were on normal duties. The results were obtained by processing data into frequencies and percentages, chi-square values and regression models. Data that were analyzed include demographic data, types of injuries sustained by sawmill workers at the Timber market, and factors influencing occupational injury among sawmill workers as well as the occupational safety standards used by saw mills at the Timber market. Results: In total, 150 respondents were sampled for this study. Generally, injuries recorded among the saw mill workers comprised injuries to the hand and legs (56%), shoulder and hand injury (12.7%), and eye injury (4.7%). Workers who were not educated were two times more likely to experience occupational injury as compared to their counterparts. Majority of the injuries occurred during wood cutting but most of the workers were not using personal protective equipment. Conclusion: Considering that majority of saw mill workers do not wear personal protective equipment, resulting to injuries during wood cutting, occupational safety education on the importants of personal protective equipment will greatly enhance occupational safety.
Thesis (MSc)
Keywords: Occupational Injuries; Sawmill Workers; Agbogbloshie; Timber Market; Accra; Ghana